2018
DOI: 10.1186/s12991-018-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction and happiness associated with depressive symptoms among university students: a cross-sectional study in Korea

Abstract: BackgroundThis cross-sectional study investigated the impact of life satisfaction and happiness, as well as the prevalence and correlates of depressive symptoms in a large sample of university students.MethodsWe included 2338 students at 6 universities in 1 metropolitan city and 2 provinces of Korea. Depressive symptoms were assessed by the Beck Depression Inventory, and scores of 16 or higher were categorized as the presence of depression. Various sociodemographic, life satisfaction, happiness, and clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 50 publications
9
51
0
2
Order By: Relevance
“…Similar results have also been found when mental health problems have been treated as the dependent variable. Seo et al ( 27 ) found in their study with South-Korean students, that both AUDIT-scores and rate of risky alcohol use (males: AUDIT ≥12, females: AUDIT ≥8) were higher in the depressed group, compared with the non-depressed group. In addition, Sæther et al ( 17 ) found that students who reported risky alcohol use (AUDIT 8-17) had slightly reduced life satisfaction and more mental health problems compared with the students who reported low risk alcohol use.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar results have also been found when mental health problems have been treated as the dependent variable. Seo et al ( 27 ) found in their study with South-Korean students, that both AUDIT-scores and rate of risky alcohol use (males: AUDIT ≥12, females: AUDIT ≥8) were higher in the depressed group, compared with the non-depressed group. In addition, Sæther et al ( 17 ) found that students who reported risky alcohol use (AUDIT 8-17) had slightly reduced life satisfaction and more mental health problems compared with the students who reported low risk alcohol use.…”
Section: Discussionmentioning
confidence: 93%
“…This association may be particularly relevant to investigate among students since they are in an age-period where high-prevalence mental disorders (depression, and anxiety) emerge ( 26 ). Former studies have typically found that increased levels of mental health problems lead to increased alcohol consumption ( 25 ) or reversed ( 27 ). A particular relevant study was done by Sæther et al ( 17 ), who used data from the Norwegian SHoT 2014 survey.…”
Section: Introductionmentioning
confidence: 99%
“…Such a finding was also aligned in the path analysis, whereby we found evidence on the negative linear relationship between happiness with the three mental health constructs. Likewise, a large-scale cross-sectional study on 2,383 university students in Korea whereby happiness is associated with lower risk of depression symptoms ( 33 ). For decades, the field of clinical psychology has primarily focused on problems and deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research found that university students' satisfaction with life and have negative correlation with depression. Their ndings suggest that to improve the satisfaction with life is to focus on the effective intervention and manage depression issue among the university students [19,20].…”
Section: Introductionmentioning
confidence: 99%